Evaluation of the Deaths due to Traffic Accidents in Adana - Hilal, Ahmet; Meral, Demet; Arslan, Muhammet Mustafa; Gülmen, Mete; Eryılmaz, Mehmet; Karanfil, Ramazan (The Bulletin of Legal Medicine, 2004)
Traffic accidents play important role in the daily routine of forensic practices. Thousands of people die or get injured due to traffic accidents each year. Traffic accidents and the data must be very well over viewed and analyzed for to assure correct protective and preventive safeties. In this study we have analyzed the data of the Adana District Attorney, the Legal Medicine Branch and Morgue Unit of the Adana Branch of the Turkish Forensic Medicine Council between the dates 01.01.2001- 31.12.2004. The cases have been evaluated by age, gender, cause of death and place where death took place. There were 3516 cases in total. 1269 (36.1 % ) of them died due to traffic accidents. Ninehundred sixtysix (76.1 %) were male while 303 (23.9 %) of them were female. The age range was starting from two days old to 90 years. The mean value was 37.6. The majority of the cases were pedestrians with 576 (45.4 %) cases. Most of the deaths were in between the ages of 0-10 with 205 (16.2 %) cases. Key Words: Traffic accidents, death, postmortem examination.